1979
DOI: 10.1063/1.325831
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-diffusion-rate-limited hydriding and dehydriding kinetics

Abstract: Hydriding and dehydriding kinetics are derived within the framework of the Johnson-Mehl-Avrami equation. Hydriding is considered to be rate limited by hydrogen diffusion through a growing hydride layer, and dehydriding by hydrogen diffusion through a growing metal layer. Incubation time effects due to surface contamination are taken into account by a delayed nucleation function. The dominant composition-dependent terms in the thermodynamics and in the mobility are taken into account to derive normative diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(49 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Apart from the geometrical suggestion, it was frequently reported that the finite diffusion rate of hydrogen has an effect on desorption kinetics [4]. For the current model this factor was neglected because of the very fast diffusion rate [16,17].…”
Section: Influence Of the Diffusion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the geometrical suggestion, it was frequently reported that the finite diffusion rate of hydrogen has an effect on desorption kinetics [4]. For the current model this factor was neglected because of the very fast diffusion rate [16,17].…”
Section: Influence Of the Diffusion Ratementioning
confidence: 99%
“…Conventionally, they are distinguished as in Ref. [4] 2. Diffusion through the a-phase (further in the text adiffusion), 3.…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…In order to keep roughly constant the thermodynamic driving force, estimated according to the formulation of Rudman et al [27] the cycling was induced by switching the pressure between 10 bar and 0.1 bar for 22 cycles.…”
Section: H 2 Cyclingmentioning
confidence: 99%
“…in Ref. [21]. Contrary to the conclusion often drawn, namely that the process of desorption is controlled by diffusion [12,13,16,21], quantitative data describing hydrogen diffusion itself are very sparse in the literature.…”
Section: Introductionmentioning
confidence: 86%